Design and development of digital-signal-processors-based intelligent controllers for industrial applications - Er, Meng Hwa (2008)
The objectives of this research are to develop FNN's by various techniques so that these systems can be used for on-line identification and control processes in dealing with nonlinear, time-varying, ill-defined systems.